Multi‐center study reveals impairment of cortical tissue oxygenation during rising blood CO2 tension in MCI and AD patients. (20th December 2022) - Marmarelis, Vasilis; Billinger, Sandra A; Chui, Helena C; Joe, Elizabeth B; Shin, Dae; Cardim, Danilo; Hashem, Suhaib; Aaron, Stacey E; Cullum, Munro; Kelley, Brendan J.; Zhang, Rong
Abstract: Background: An ongoing multi‐center study of a consortium of Alzheimer's Disease Centers in Los Angeles (USC), Dallas (UT‐SWMC) and Kansas City (KUMC) has explored quantitatively the dynamics of the homeostatic mechanism that maintains adequate cortical tissue oxygenation during a rise in blood CO2 tension. The results from cognitively normal subjects and MCI/AD patients were compared to assess differences in the dynamics of this important homeostatic mechanism. Method: Quantification of the dynamics of cortical tissue oxygenation was achieved through extraction of predictive models from five‐minute data‐records of spontaneous fluctuations in cortical tissue oxygenation (CTO), measured non‐invasively via near infrared spectroscopy at the prefrontal cortex, and the associated fluctuations in arterial blood pressure (ABP) and end‐tidal CO2 (etCO2). Using a novel kernel‐based modeling methodology, we analyzed the time‐series data from 25 MCI patients, 7 AD patients and 45 age‐matched cognitively normal controls (NC) and obtained predictive models of the dynamic effects of ABP and etCO2 (viewed as a proxy for blood CO2 tension) upon CTO. These predictive models were used to quantify the dynamics of cortical CO2 reactivity (CCR) in each participant, as the time‐average of the model‐predicted CTO response to unit‐step etCO2 change over the first 30 sec. The obtained CCR indices were used to evaluate the differences between NC and MCI/AD patients. Result: The obtained CCR indices were significantly different for the 32 patients (MCI and AD lumped together due to small number of AD) vs. 45 age‐matched controls (p= 0.0083), with respective mean (SD): 0.014 (0.108) vs ‐0.059 (0.119). This is illustrated in Figure 1, where the average model‐predicted CTO responses to a unit‐step change of etCO2 are shown for 32 MCI/AD patients (red line) and 45 controls (blue line). Note the negative values of the average CTO response for patients (red line) to unit‐step increase of etCO2 that indicates polarity reversal of the normal CO2 vasomotor reactivity (blue line). Conclusion: Quantitative analysis of cortical oxygenation dynamics under resting spontaneous conditions in 32 MCI/AD patients relative to 45 age‐matched controls revealed a significant impairment of the homeostatic mechanism that maintains adequate oxygenation of cortical tissue during a rise in blood CO2 tension.